Evaluation of Chronic Energy Deficiency (KEK) Management Program for Pregnant Women in the Work Area of Puskesmas, Polewali Mandar Regency (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to evaluate the program to overcome chronic energy deficiency in pregnant women. Adescriptive qualitative research with an evaluation study approach. Interviews were conducted with 6 key informantsand 2 pregnant women. Data collection techniques used in-depth interview techniques, observation techniques anddocumentation techniques. The validity of the data using triangulation, namely triangulation of data sources,triangulation of theories, and triangulation of methods. The results of research on prevention of KEK in pregnantwomen, the input component shows 3 indicators that have not been met, and the emergence of policies with the aimof producing healthy mothers and children. Meanwhile, in the process of organizing, monitoring and mobilizingwhich is lacking and still weak in carrying out their respective functions and responsibilities, it is hoped that specialattention from the government, especially the health department, can run optimally where the overall indicators ofthe program to overcome chronic energy deficiency in pregnant women show that program coverage has not reachedthe target that has been set and the discovery of the status of cake in pregnant women is still high in addition to theimpact of the pandemic that increases young marriages. Insufficient and weak supervision and mobilization incarrying out their respective functions and responsibilities, it is hoped that special attention from the government,especially the health department, can run optimally where the overall indicators of the program to overcome chronicenergy deficiency in pregnant women indicate that the program coverage has not reached the target. which havebeen set. And the discovery of the status of cake in pregnant women is still high in addition to the impact of thepandemic that increases young marriages. Insufficient and weak supervision and mobilization in carrying out theirrespective functions and responsibilities, it is hoped that special attention from the government, especially the healthdepartment, can run optimally where the overall indicators of the program to overcome chronic energy deficiency inpregnant women indicate that the program coverage has not reached the target. which have been set. And thediscovery of the status of cake in pregnant women is still high in addition to the impact of the pandemic thatincreases young marriages.